Pengaruh Transparansi, Akuntabilitas Dan Sistem Pengendalian Internal Terhadap Pengelolaan Keuangan Dana Desa - Junanda, Yorhi; Serly, Vanica (Universitas Negeri Padang, 2025)
In an empirical study in villages in Pariaman City, the purpose of this study is to determine the effect of Transparency, Accountability and Internal Control System on Financial Management of Funds (Empirical Study in villages in Pariaman City). In this study, the population used was 55 villages located in Pariaman City. The number of samples was taken using the purposive sampling method. To calculate the number of samples, the Issac and Michael formula was used to obtain 117 staff members from the village. This is a type of quantitative research, and the data source in this study is primary data distributed to village officials in Pariaman City through a questionnaire. The results of this study indicate that transparency has no effect, accountability and internal control systems have an effect on village fund management.